Development Of Physics Learning Media PHY-ART (Physics With Augmented Reality Technology) To Empower Student’s Laboratory Skills - Batulieu Muhammad Yoggi Prastya; Sri Budiawanti; Daru Wahyuningsih (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The world of education requires newest learning media when technology is growing. The development of Physics learning media with Augmented Reality technology is a solution to bring forward education. The development of Physics learning media PHY-ART aims to describe the development of Augmented Reality technology for physics learning media, and find out the impact of implementing Physics learning media PHY-ART on improving students' laboratory skills. A total of 78 high school students were researched with pre-test and post-test to determine the students' laboratory skills before and after. After using Physics learning media PHY-ART, it is known that AR technology improves students' laboratory skills. The physics learning media PHY-ART can be used by educational practitioners to improve laboratory skills and can be used as an alternative in the variety of learning media.